1987
DOI: 10.1083/jcb.104.3.655
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in myelin-induced proliferation of cultured Schwann cells.

Abstract: Abstract. Schwann cell proliferation induced by a myelin-enriched fraction was examined in vitro. Although nearly all the Schwann cells contained material that was recognized by antisera to myelin basic protein after 24 h, only 1% of the cells were synthesizing DNA. 72 h after the addition of the mitogen a maximum of 10% of the cells incorporated [3H]thymidine. If the cultures were treated with the myelin-enriched fraction for 24 h and then washed, the number of proliferating Schwann cells decreased by 75 % wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Much evidence has shown that the digestive process of myelin is intimately related to Schwann cell proliferation (1,2,5,8,11,20,21). The removal of the myelin sheath elicited proliferative response of Schwann cells (5,12,16).…”
mentioning
confidence: 99%
“…Much evidence has shown that the digestive process of myelin is intimately related to Schwann cell proliferation (1,2,5,8,11,20,21). The removal of the myelin sheath elicited proliferative response of Schwann cells (5,12,16).…”
mentioning
confidence: 99%
“…lb) might then result from an increased level of mitogenic factors pro vided by the degrading myelin. A similar age-related in crease has also been described in myelin-induced pro liferation of rat Schwann cells [40]. Conversely, the low rate of Trembler Schwann cell division would be corre lated with the reduced amount of degradable myelin present in mutant nerves at the time they are plated.…”
Section: Age-related Proliferation O F Schwann Cellsmentioning
confidence: 69%
“…The proliferation of secondary mouse quiescent Schwann cells started only 48 h after myelin was added to the medium, as shown in rat Schwann cell cultures [40]. At day 1, few nuclei were labeled.…”
Section: Mitogenic Effects O F Nerve and Myelin Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…After differentiation, Schwann cells phagocytize myelin debris. Lysosome-processed myelin debris then acts as an inducer and activator for resident macrophages [7,12,29]. Differentiated and activated Schwann cells and macrophages produce neurotrophic factors that accelerate axonal sprouting and outgrowth [21], while proliferating Schwann cells arrange themselves to form tubes to guide regenerating axons.…”
Section: Discussionmentioning
confidence: 99%